2003
DOI: 10.1108/09604520310456726
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of service quality and product quality and their influences on bank reputation: evidence from the banking industry in China

Abstract: Although an increasing number of studies is being performed in the field of service management, less work is being done on an integrated framework of service quality and product quality, especially that supported with evidence from developing countries. As a result, little is known about the distinction between service quality and product quality, their respective antecedents, and their distinctive contributions to performance in service industries in the developing world. Generalization of related findings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
214
1
32

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(265 citation statements)
references
References 32 publications
7
214
1
32
Order By: Relevance
“…Customer satisfaction is highly related with service quality as service quality improves the probability of customer satisfaction [5], this results in commitment, intent to stay (customer retention), creation of a mutually rewarding relationship (bond) between the service provider and the user, increased customer tolerance for service failure and positive word-of-mouth advertising about the organization [32][33][34]. Banks now know that delivering quality service to customer is essential for success and survival in today's global and competitive banking environment [35].…”
Section: Customer Service Qualitymentioning
confidence: 99%
“…Customer satisfaction is highly related with service quality as service quality improves the probability of customer satisfaction [5], this results in commitment, intent to stay (customer retention), creation of a mutually rewarding relationship (bond) between the service provider and the user, increased customer tolerance for service failure and positive word-of-mouth advertising about the organization [32][33][34]. Banks now know that delivering quality service to customer is essential for success and survival in today's global and competitive banking environment [35].…”
Section: Customer Service Qualitymentioning
confidence: 99%
“…Similarly, by engaging in activities beyond their formal role prescriptions such as assisting their colleagues that are temporarily burdened with work, providing informal mentoring for lesser skilled staffs, and displaying acts of courtesy and goodwill to customers, customer-contact employees are bound to contribute to better service. According to Wang et al (2003), superior service quality will have positive consequences in the form of enhanced reputation, higher customer satisfaction and retention, and greater profitability for the service organization.…”
Section: Introductionmentioning
confidence: 99%
“…Aldlaigan and Buttle (2002) introduced the SYSTRA-SQ model. Wang et al (2003) argued that in the banking industry, the purchasing and repurchasing behaviour of costumers are correlated to the reputation of the financial service provider. Arasil et al (2005) focused on Greek Cypriot banks revealed that the customer satisfaction level is heavily dependent on the people who deliver the service.…”
Section: Servqual Model and Its Role In Measuring Service Quality In mentioning
confidence: 99%